Language Patterns and Attitudes of Kinamiging Manobo Speakers - Alamillo, John Brian; Talili, Ismael (JPAIR Multidisciplinary Research, 2016)
Language diversity reflects a society’s richness in culture. Kinamiging Manobo, a language spoken in the southern Philippines, faces a threat of extinction posed by a more dominant language. The study aimed to determine the language patterns and the attitude of the speakers towards their language and the survival probability of the language. The descriptive research involved 40 respondents who resided in Sagay, Camiguin Island - a bilingual community. The study utilized two instruments, namely, sociolinguistic survey questionnaire and matched-guise technique. The sociolinguistic survey questionnaire was adapted from the study of Campos (2014), who investigated the attitudes of Agusan Manobo speakers towards their language. Results show that Kinamiging Manobo is no longer used in most of the respondents’ sociolinguistic domains. The findings support the claims that the language is classified as a threatened language. Speakers of Kinamiging Manobo prefer to use Cebuano in all the sociolinguistic domains (home, friendship, public and religious). However, most speakers have positive attitudes towards their language and are willing to do necessary efforts to preserve it. Kinamiging Manobo is least used in church, and is more often used (but still not the dominant language) at home.